2017
DOI: 10.4236/nm.2017.81001
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Imaging Techniques in Lhermitte-Duclos Disease (LDD): A Case Report and Brief Literature Review

Abstract: Lhermitte-Duclos disease (LDD), also called dysplastic gangliocytoma of the cerebellum, is a rare condition described in 1920. It represents a disorganization of cerebellar architecture with overgrowth of cerebellar ganglion cells which replace granular cells and Purkinje cells. In this report we present the case of a 62-year-old male affected by this disease, as well as literature review of the clinical, morphological and functional radiological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The low Cho/NAA ratio has been linked to the diagnosis of LDD [6] . However, non-significant MRS findings in LDD have been reported [16] , just as in our patient.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The low Cho/NAA ratio has been linked to the diagnosis of LDD [6] . However, non-significant MRS findings in LDD have been reported [16] , just as in our patient.…”
Section: Discussionsupporting
confidence: 46%
“…DWI and ADC images in our patient showed no diffusion restriction. Some LDD cases showed diffusion restriction, likely due to hypercellularity and dense collection of axons [16] . While cases of LDD showing increased cerebral blood flow on perfusion studies have been reported [11] , our patient perfusion studies showed no significant elevation in cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 5 reports are Brazilian. [9][10][11][12][13][14] Therefore, this article is the 6th report of LDD and the first to report the association with CS in Brazil.…”
Section: Discussionmentioning
confidence: 99%